Prenatal diagnosis, management, and outcomes of fetuses with tetralogy of Fallot in China after prenatal counseling: a prospective cohort study - Deng, Deng-pu; Qian, Tao; Liu, Yu-hong; Wu, Zhong-shi; Lu, Ting (Frontiers in Pediatrics, 2023)
Objective The study aimed to monitor fetuses with tetralogy of Fallot (TOF) after prenatal counseling and how it influenced the decision of parents to terminate the pregnancy. Methods Fetuses with isolated TOF diagnosed between January 2019 and December 2021 were prospectively enrolled. The follow-up period extended until termination or 6 months after the operation. Results Of the 1,026 fetuses diagnosed with cardiac defects, 129 were identified to have isolated TOF and completed the follow-up. A total of 55 (42.6%) fetuses were terminated, with larger maternal age (odds ratio: 0.893, 95% confidence interval: 0.806–0.989, P = 0.031) as the protective factor. The maternal anxiety score, gestational weeks, and pulmonary-to-aortic-diameter ratio lost significance in multivariate analysis. Subjectively, the two most common reasons for terminating the pregnancy were worries about the prognosis (41.8%) and concerns about the possible suffering of the unborn child (18.2%). The prenatal diagnosis was accurate in 73 of the 74 (98.6%) live births. Out of the 64 live births that underwent surgical repair in our center, 57 (89.1%) received primary repair, with a median age of 104 days, and 49 (76.6%) underwent valve-sparing repair. No perioperative death occurred. Conclusions Termination for fetuses with TOF remains common in China. Live births with TOF can be safely and effectively managed.